2,4-Di-tert-butylphenol (2,4-DTBP) purified from streptomyces sp. KCA1 from phyllanthus niruri: isolation, characterization, antibacterial and anticancer properties - Seenivasan, Ayswarya; Manikkam, Radhakrishnan; Kaari, Manigundan; Sahu, Amit Kumar; Said, Madhukar; Dastager, Syed G. (Journal of King Saud University Science, 2022)
Objectives: The present study reports the bioactivity of 2,4-Di-tert-butylphenol (2,4-DTBP) purified from an endophytic Streptomyces species KCA1 isolated from the leaves of Phyllanthus niruri and its antibacterial and anticancer properties. Methods: The extracellular metabolites were produced from the strain KCA1 by submerged fermentation using ethyl acetate. The crude extract was further evaluated for antibacterial activity against set of pathogens. Active metabolite from the extract was purified using chromatography techniques and detected its antibacterial activity by disc diffusion assay. The molecular structure of the active molecule was identified through various spectral study. Moreover, the bioactive metabolite 2,4-DTBP was analyzed antibacterial and anti-proliferative activity. Results: Strain KCA1 was identified as Streptomyces sp. In the preliminary screening, the crude extract exhibited broad spectrum activity against various bacterial pathogens. Based on the spectral properties, the active metabolite was identified as 2,4-Di-tert-butylphenol. The MIC of active compound 2,4-DTBP inhibited E. coli ATCC 25922 and S. aureus ATCC 29213 at 50 lg/ml and 0.78 lg/ml, respectively. The IC50 value of 2,4-DTBP was found to be 11.0 lg/ml and 116.8 lg/ml, against breast cancer cell line (MCF7) and normal VERO cell line, respectively. Conclusions: This study concluded that 2,4-DTBP, produced from the endophytic Streptomyces sp. KCA1, is the potential candidate to develop as promising antibacterial and anticancer agent. (C) 2022 The Authors. Published by Elsevier B.V. on behalf of King Saud University.
Keywords: 2; 4-Di-tert-butylphenol; Antibacterial; antiproliferative activity; Endophytic Streptomyces

Antibacterial and anti-HIV metabolites from marine streptomyces albus MAB56 isolated from Andaman and Nicobar Islands, India - Manikkam, Radhakrishnan; Murthy, Sangeetha; Palaniappan, Sivasankar; Kaari, Manigundan; Sahu, Amit Kumar; Said, Madhukar; Ganesan, Vijayalakshmi; Kannan, Sivakumar; Ramasamy, Balagurunathan; Thirugnanasambandan, Somasundaram; Dastager, Syed G.; Hanna, Luke Elizabeth; et al. (Applied Biochemistry and Biotechnology, 2023)
Marine-derived actinobacteria have tremendous potential to produce novel metabolites with diverse biological activities. The Andaman coast of India has a lot of microbial diversity, but it is still a relatively unknown ecology for isolating novel actinobacteria with beneficial bioactive compounds. We have isolated 568 actinobacterial strains from mangrove rhizosphere sediments and sponge samples. Crude extracts from 75 distinct strains were produced by agar surface fermentation and extracted using ethyl acetate. In the disc diffusion method, 25 actinobacterial strains showed antimicrobial activity; notably, the strain MAB56 demonstrated promising broad-spectrum activity. Strain MAB56 was identified as Streptomyces albus by cultural, microscopic, and molecular methods. Conditions for bioactive metabolites from MAB56 were optimized and produced in a lab-scale fermenter. Three active metabolites (C1, C2, and C3) that showed promising broad-spectrum antimicrobial activity were isolated through HPLC-based purification. Based on the UV, FT-IR, NMR, and LC-MS analysis, the chemical nature of the active compounds was confirmed as 12-methyltetradecanoic acid (C1), palmitic acid (C2), and tridecanoic acid (C3) with molecular formulae C14H28O2, C16H32O2, and C13H26O2, respectively. Interestingly, palmitic acid (C2) also exhibited anti-HIV activity with an IC50 value of < 1 mu g/ml. Our findings reveal that the actinobacteria from the Andaman marine ecosystems are promising for isolating anti-infective metabolites.
Keywords: actinobacteria; Andaman Islands; anti-HIV; Antibacterial; Bioactive metabolites

Novel finding: 2,4-Di-tert-butylphenol from streptomyces bacillaris ANS2 effective against mycobacterium tuberculosis and cancer cell lines - Kaari, Manigundan; Joseph, Jerrine; Manikkam, Radhakrishnan; Kalyanasundaram, Revathy; Sivaraj, Anbarasu; Anbalmani, Sivarajan; Murthy, Sangeetha; Sahu, Amit Kumar; Said, Madhukar; Dastager, Syed G.; Ramasamy, Balagurunathan (Applied Biochemistry and Biotechnology, 2023)
The aim of the present study is to identify actinobacteria Streptomyces bacillaris ANS2 as the source of the potentially beneficial compound 2,4-di-tert-butylphenol, describe its chemical components, and assess its anti-tubercular (TB) and anti-cancer properties. Ethyl acetate was used in the agar surface fermentation of S. bacillaris ANS2 to produce the bioactive metabolites. Using various chromatographic and spectroscopy analyses, the potential bioactive metabolite separated and identified as 2,4-di-tert-butylphenol (2,4-DTBP). The lead compound 2,4-DTBP inhibited 78% and 74% of relative light unit (RLU) decrease against MDR Mycobacterium tuberculosis at 100ug/ml and 50ug/ml concentrations, respectively. The Wayne model was used to assess the latent/dormant potential in M. tuberculosis H37RV at various doses, and the MIC for the isolated molecule was found to be 100ug/ml. Furthermore, the molecular docking of 2,4-DTBP was docked using Autodock Vinasuite onto the substrate binding site of the target Mycobacterium lysine aminotransferase (LAT) and the grid box was configured for the docking run to cover the whole LAT dimer interface. At a dosage of 1 mg/ml, the anti-cancer activity of the compound 2,4-DTBP was 88% and 89% inhibited against the HT 29 (colon cancer) and HeLa (cervical cancer) cell lines. According to our literature survey, this present finding may be the first report on anti-TB activity of 2,4-DTBP and has the potential to become an effective natural source and the promising pharmaceutical drug in the future.
Keywords: 2; 4-Di-tert-butylphenol; anti-cancer; Anti-tubercular; Molecular docking; Streptomyces bacillaris

Integrated genomic and functional analysis of Streptomyces sp. UP1A-1 for bacterial wilt control and solanaceae yield increase - Kaari, Manigundan; Manikkam, Radhakrishnan; Joseph, Jerrine; Krishnan, Sakthivel; Annamalai, Kishore Kumar; Khan, Abujunaid; Rajput, Vinay; Dastager, Syed Gulam; Dharne, Mahesh S.; Umar, Md; Venugopal, Gopikrishnan; Alexander, Balamurugan (Gene Reports, 2024)
<em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Ralstonia solanacearum<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> is one of the most destructive soil-borne pathogen, causing bacterial wilt to the solanaceae vegetables. <em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Streptomyces<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> sp. UP1A-1 isolated from healthy solanaceae rhizosphere soil, exhibited the lowest disease incidence and increased fruit yield of solanaceae vegetables. However, the genomic and functional properties of UP1A-1 are unclear. Therefore, we conducted the present study to elucidate the genomic characteristics of UP1A-1 by whole genome sequencing. The results indicate that the genome of <em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Streptomyces<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> sp. UP1A-1 consists of 8,252,902 bp and contains 72.42 % G + C. We identified the genes that confer plant growth promoting (PGP) function, which include those involved in siderophore production, indole-3-acetic acid biosynthesis, phosphate solubilization, nitrogen metabolism, and potassium metabolism. We also identified several other genes, such as chitinase, peroxidase, superoxide dismutase, catalase, proline biosynthesis, and glucose dehydrogenase, which are believed to be involved in the control of wilt disease. These genes revealed that the strain UP1A-1 has physiologically adapted to varied environmental conditions and could potentially control both abiotic and biotic stresses.